PENGARUH PERTUMBUHAN EKONOMI, PAD, DAU, DAK, DAN DBH TERHADAP BELANJA MODAL DI KABUPATEN/KOTA JAWA BARAT TAHUN 2019-2021 - Twinki, Bela Sania; Widiyanti, Dwi Retno (Journal of Development Economic and Social Studies, 2023)
This study aimed at determining the influence of the Economic Growth, Local Own-Source Revenue, General Allocation Fund, Special Allocation Fund, Profit-Sharing Fund on Capital Expenditures in Regencies and Cities in West Java during the 2019-2021 period. The data analysis methods in this study used panel data regression, using CEM, FEM, and REM. Type of approach method to spesific model test is Chow Test, Hausman Test, and Lagrange Multiplier Test. Used classic assumption test is Normality Test, Autokorelasi Test, Multikolinearitas Test, and Heteroskedastisitas Test. Next, hypothesis test using T Test, F Test, and Coefficient of Determination (R2). The result of the research show that Economic Growth, PAD, DAU, DAK, and DBH have significant influence to Capital Expenditure. Economic Growth, PAD, and DAU have positive and significant influence to Capital Expenditure. DBH have negative and significant influence to Capital Expenditure. Meanwhile, DAK does not have influence to Capital Expenditure.